Evaluasi Kesesuaian Lahan Kecamatan Tompobulu Kabupaten Bantaeng untuk Pengembangan Tanaman Lada (Piper nigrum L) - Muhammad Iqbal; Hazairin Zubair; Rismaneswati Rismaneswati (Jurnal Ecosolum, 2018)
Potential land resources can be expected through land evaluation activities. This study aims to evaluate the suitability of Tompobulu Subdistrict of Bantaeng Regency for the development of pepper plant (Piper nigrum L). This research was conducted in Tompobulu Sub-district of Bantaeng Regency which started from March to July 2016. This research used qualitative method and to determine land suitability using simple limiting factor approach. Determination of observation points based on the overlapping results of the baseline maps that resulted in 6 units of observation (soil profile). Production data and management of pepper crop obtained from farmers of respondents amounted to 10 people. The result of the study shows that the climate type of the research area according to Oldeman is classified as B2 with the actual land suitability class which is quite suitable (S2) with 3,657 Ha and the marginal fit (S3) with 3,023 Ha with rainfall limiting factor, soil depth, Slope, and surface rocks whereas the suitability class is quite suitable (S2) with an area of 6,160 Ha and corresponding marginally (S3) with an area of 520 Ha with rainfall and soil depth limiting factors. The potential of pepper plant development in Tompobulu Sub-district of Bantaeng Regency is quite large indicated by the percentage of land area that is quite suitable (S2) (82.40%).